Female Masculinity in Indonesian Folklore Nyai Undang Ratu Rupawan dari Pulau Kupang - Siswantia Sar (MUWAZAH : jurnal kajian gender, 2020)
This paper aims to explore the female masculinity in Indonesian folklore from Central Kalimantan, Nyai Undang Ratu Rupawan dari Pulau Kupang. This research uses gender study, masculinity. The material object in this study is a folklore originating from Kupang Island, Central Kalimantan, entitled Nyai Undang Ratu Rupawan dari Pulau Kupang. The formal object of this research is gender study, masculinity. Data analysis was performed through qualitative descriptive techniques by interpreting the data found in Nyai Undang Ratu Rupawan dari Pulau Kupang folklore and linked to masculinity data. Masculinity is generally associated with men. However, masculinity is not nature carried by children when they were born. It does not only belong to men. Females can also have masculine traits as it is not something absolute and fixed but merely a construction. Women and men are labeled with gender identities and values by culture and society. This paper tries to highlight how masculinity in Nyai Undang is relevant to the masculinity that exists in Dayak women in Central Kalimantan. Nyai Undang is a Dayak woman who has some traits that are considered masculine including leadership skills, courage, and assertiveness. This research eventually finds out that these masculine qualities that are found in Nyai Undang can also be found in Dayak women in Kalimantan.